Assessing learning preferences of dental students using visual, auditory, reading-writing, and kinesthetic questionnaire - Darshana Bennadi; K R Kashinath; J V Bharateesh; Nandita Kshetrimayum (Wolters Kluwer Medknow Publications, 2015)
Introduction: Educators of the health care profession (teachers) are committed in preparing future health care providers, but are facing many challenges in transmitting their ever expanding knowledge to the students. This study was done to focus on different learning styles among dental students. Aim: To assess different learning preferences among dental students. Materials and Methods: This is a descriptive cross-sectional questionnaire study using visual, auditory, reading-writing, and kinesthetic questionnaire among dental students. Results: Majority 75.8% of the students preferred multimodal learning style. Multimodal learning was common among clinical students. No statistical significant difference of learning styles in relation to gender (P > 0.05). Conclusion: In the present study, majority of students preferred multimodal learning preference. Knowledge about the learning style preference of different profession can help to enhance the teaching method for the students.